The effect of the application of Albert Bandura’s behaviorism theory on the motivation and learning outcomes - Hardiyana, Minati Rina; Maemonah, Maemonah (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2023)
A teacher must be able to understand the theory of learning and learning in order to understand, motivate, and influence the motivation and learning outcomes of his students; behavioristic learning theory is one developed by Albert Bandura. This article aims to find out how the implementation of the Behaviorism theory approach from Albert Bandura affects student motivation and learning outcomes. Sampling in quantitative research using the Quasi-Experimental method using pretest, posttest, and control groups. The research design was tried using the saturated sampling method. The initial sample consisted of all VB class students, with a total of 25 students as a control class, and the second illustration consisted of all VA class students, with a total of 28 students as an experimental class. The results of the analysis show that the implementation of Albert Bandura's behaviorism theory approach using the experimental class MANOVA test gives significant results namely 0.011 is smaller than 0.05, so H0 is rejected and H1 is accepted. Based on this, there is an influence on the application of Albert Bandura's theoretical approach to student motivation and learning outcomes